Error analysis of the language transfer in Grammar construction of the brain - Andi Ummul Khair (Center for Humanities and Innovation Studies, 2018)
This study attempts to analyze the reason for students making fossilized errors on the sentence uttered in their effort of language transfer and related it with the grammar construction in the brain. Fifty-six students participated in this study. The technique used to collect the data is an analysis of transcription on conversation video. This study found out that the students make those due to their active trial in making sense of the limited knowledge of the language they are exposed to in the brain in order to express some phrases systematically. Thus, learners need to enrich out the input of target language from the native language resources which can be gained from many kinds of authentic material; those are music, movie, games, advertisement, and information of the stuff. This study is expected to be a reference for the future research to find the best way in stimulating learners in acquiring grammar of L2 sentence considering that they need maturity in the regular changing sequence of acquisition of morpho-syntactical structures, impervious to teaching.